Ethnobotany of Food Plants Used by Local Communities at Joben Resort Mount Rinjani National Park, East Lombok - Ahmad Jupri; Erika Wulan Milenia; Wardatul Jannah; Pahmi Husain (Jurnal Biologi Tropis, 2022)
The use of food plant species by local communities is very important to study using the concept of ethnobotany. The purpose of this study was to determine the diversity of plant species, the use of food plants and how to process them at the Joben Resort, Mount Rinjani National Park. This research method is a field survey method which consists of interviews, observations, identification of plant species and data analysis. Determination of the sample using purposive sampling technique. Data was collected through semi-structured interviews and then collected plant specimens accompanied by key informants. Data analysis was carried out descriptively qualitatively after being processed in Microsoft Excel using simple statistical techniques. Based on the results of the study showed that there were 10 types of food plants obtained from the forest of Joben are: Goa (Ficus variegata), Cinnamon (Cinnamomum Burmannii), Jackfruit (Artocarpus heterophyllus), Candlenut (Aleurites moluccana), Salam (Syzygium polyanthum), Kentawong/Sintrong (Crassocephalum crepidioides), Jelijo/Tempuh Wiyang (Emilia sonchifolia), Fern (Diplazium esculentum), Bujak (Hedychium coronarium), and Jee/Putat (Planchonia valida). Utilization of food plants, among others, dried, made into spices, made into vegetables, direct consumption and sold. The most dominant use was fern 26%, followed by Jackfruit 21% and Salam 14%. Then the use of jackfruit plants was relatively large (20%) which could be used as vegetables, eaten directly and sold. Meanwhile, the most widely used plant parts were the leaves of food plants (66%) and fruit of food plants (21%).